Experimental study and weighting analysis of factors influencing gas desorption - He, Xin; Cui, Hong-qing; Zhang, Hang; Wang, Zhen-zhi; Wang, Ze-hua; Shi, Guang-shan (Frontiers in Earth Science, 2023)
Gas is one of the necessary contributing factors for coal and gas outburst accidents, and the gas desorbed in coal is the energy carrier in the outburst process. The study of gas desorption laws is the premise and basis for gas content determination and gas accident prevention. To solve the problem of inaccurate gas content measurement due to the unclear characteristics of rapid gas desorption in 0~10 s, the gas desorption experimental device was improved, the influence factors of gas desorption were studied experimentally, and a comprehensive analysis method was proposed based on the gas desorption rate, gas desorption efficiency, initial gas desorption amount and total desorbed gas. The experiment analysed five factors that affected gas desorption, including the degree of metamorphism, type of failure, particle size, pressure and temperature. The results show that there is a monotonically decreasing power function relationship between the initial gas desorption rate and time and a monotonically increasing logarithmic function relationship between the gas desorption amount and time; the curve has a limit value. The gas desorption amount is large in 0~10 s and increases slowly afterwards. Among the factors affecting gas desorption, their importance decreases in the order of pressure > metamorphism > particle size > failure type > temperature. This study is of great practical value for the calculation of gas losses in gas content determination, and the resulting gas desorption laws are of great importance in guiding gas control work.